Variation in the sensitivities of hairy Beggarticks (Bidens pilosa) plants and their progenies to glufosinate ammonium - De Brito, Ivana P.F.S. [UNESP]; Marchesi, Bruna B. [UNESP]; Pucci, Carolina [UNESP]; Carbonari, Caio A. [UNESP]; Velini, Edivaldo D. [UNESP] (Cambridge University Press (CUP), 2016)
The objective of this study was to evaluate the response of hairy beggarticks plants to different doses of glufosinate ammonium and the range in sensitivities of the plants and their progenies to the herbicide. Three studies were conducted, all in a greenhouse and repeated at different times. In the first study, two experiments were conducted to examine the dose-response curve, and the treatments were seven different doses of the herbicide glufosinate ammonium (0, 50, 100, 200, 400, 800, and 1,600 g ai ha-1), with four replications each. In the second study, which examined the range in sensitivity of hairy beggarticks to glufosinate ammonium, 44 plants were sprayed with a dose of 200 g ai ha-1 of the herbicide. Finally, in the third study, the range in sensitivity of the progeny of hairy beggarticks to glufosinate ammonium was investigated; in this experiment, the progenies of seven of the previous plants were sprayed with 200 g ai ha-1 of herbicide. The ammonium contents in the tissues were measured and percent injury wase visually assessed. Ammoniun content in hairy beggarticks leaves was increased more than seven times by glufosinate application and the maximum ammonium content was observed for the highest dose of the herbicide. Variability existed in the ammonium content among the individuals of the population of hairy beggarticks; however, the behavior was not replicated in the same way in the progenies. The survival of the plants after application of the herbicide allows the production of progenies with wide variability in their sensitivity to the product, independent of the behavior for the progenitor plants.
Keywords: Ammonia; black-jack; differential sensitivity; glutamine synthetase.